Comparison of learning civic(s) education in Indonesia with Japan - Andriyana Andriyana; Iim Siti Masyitoh (Journal of Social Studies (JSS), 2018)
Japan is a country with a quality education system and quality in the process of education and learning. Education in Japan implement standards and learning good management and structured coherently, including in the areas of learning Civic(s) Education. This study aims to provide comparative study Civic(s) Education in Indonesia with Japan. The method used in this research is a comparative study with a qualitative approach. The study was conducted in Bandung Japanese School. Informants consisted Japanese teacher of Civic(s) Education in Indonesia, Indonesian teacher of Civic(s) Education and Japanese lecturers in Indonesia. The collected data of this research obtained through interview, observation, literature and documentation then analyzed by analytical techniques such as data reduction, data presentation, and verification and validation using triangulation techniques and data collection techniques. The results showed that there are differences and similarities that exist in learning Civic(s) Education in Indonesia and Japan. Differences exist which of the methods used in the learning process, which in Indonesia using the method of lecture and discussion, while in Japan using a method that emphasizes living experience of learners in exploring the material obtained. And there are similarities in the structure of scientific disciplines Civic(s) Education in Indonesia and Japan are detached (separated) from the disciplines of social (Social Studies) and also in the purpose and role of the Civic(s) Education In shaping citizens' competence in the flow of globalization as well as moral education and character development of citizens.